Teramnus Labialis (L.f.) Spreng seeds priming with an organic agent: Effects on germination and initial seedling growth - Lisbet Bolaño; Yanier Acosta; Gustavo Yasser Lorente; Lianny Pérez-Gómez; Paula Fernandes; José Carlos Lorenzo; Carlos Mazorra; Dayami Fontes (Agrociencia Uruguay)
Teramnus labialis (L.f.) Spreng is a forage legume that is used for animal feed and as a cover crop in various fruit species. However, the seeds have a low germination percentage and after the emergence of the seedling establishment is difficult due to their slow growth. Seed priming treatments are an alternative to improve germination and vigor of seedlings during the initial growth phase. The objective of the present investigation was to determine the effectiveness of the use of IHPLUSTM for priming of T. labialis seeds. The seeds were primed with IHPLUSTM at a concentration of 5% for 3 h and its effect was evaluated during germination and on the seedlings after 14 days of cultivation under semi-controlled conditions. Priming with IHPLUSTM increased the germination percentage (from 72% to 94%) and reinvigorated the seeds. The concentration and mobilization of amino acids during germination increased after seed priming. Additionally, after 14 days of growth, the seedlings obtained from the conditioned seeds increase the fresh (from 14.43 mg to 18.69 mg) and dry mass (from 4.93 mg to 6.33 mg), the length and thickness of the stem, the number of leaves, as well as the length of the root. Therefore, the priming of T. labialis seeds with IHPLUSTM is effective in increasing germination and improving seedling vigor during the initial phase of growth.